Triflic acid catalyzed oxidative lactonization and diacetoxylation of alkenes using peroxyacids as oxidants - Kang, Yanbiao; Gade, Lutz H. (The journal of organic chemistry, 2012)
A clean and efficient diacetoxylation reaction of alkenes catalyzed by triflic acid using commercially available peroxyacids as the oxidants has been developed. This method was also applied in oxidative lactonizations of unsaturated carboxylic acids in good to high yields.